Azimuthal angle correlations of muons produced via heavy-flavor decays in 5.02 TeV Pb + Pb and pp collisions with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physical review letters, 2024)
Angular correlations between heavy quarks provide a unique probe of the quark-gluon plasma created in ultrarelativistic heavy-ion collisions. Results are presented of a measurement of the azimuthal angle correlations between muons originating from semileptonic decays of heavy quarks produced in 5.02 TeV Pb+Pb and 𝑝⁢𝑝 collisions at the LHC. The muons are measured with transverse momenta and pseudorapidities satisfying 𝑝𝜇T>4 GeV and |𝜂𝜇|<2.4, respectively. The distributions of azimuthal angle separation Δ⁢𝜙 for muon pairs having pseudorapidity separation |Δ⁢𝜂|>0.8, are measured in different Pb +Pb centrality intervals and compared to the same distribution measured in 𝑝⁢𝑝 collisions at the same center-of-mass energy. Results are presented separately for muon pairs with opposite-sign charges, same-sign charges, and all pairs. A clear peak is observed in all Δ⁢𝜙 distributions at Δ⁢𝜙∼𝜋, consistent with the parent heavy-quark pairs being produced via hard-scattering processes. The widths of that peak, characterized using Cauchy-Lorentz fits to the Δ⁢𝜙 distributions, are found to not vary significantly as a function of Pb +Pb collision centrality and are similar for 𝑝⁢𝑝 and Pb +Pb collisions. This observation will provide important constraints on theoretical descriptions of heavy-quark interactions with the quark-gluon plasma.
Gesehen am 25.06.2025
ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S. M. Weber, M. Wessels, J. Zinsser [und 2924 weitere]
Im Titel ist "pp" kursiv geschrieben